Fiber-reinforced composites : materials, manufacturing, and design - Mallick, P. K., 1946- (Dekker mechanical engineering., 2008)
This edition provides comprehensive discussions of all aspects of fiber-reinforced composites, including materials, mechanics, properties, test methods, manufacturing, and design.